2016
DOI: 10.3390/md14050103
|View full text |Cite
|
Sign up to set email alerts
|

Time Dependency of Chemodiversity and Biosynthetic Pathways: An LC-MS Metabolomic Study of Marine-Sourced Penicillium

Abstract: This work aimed at studying metabolome variations of marine fungal strains along their growth to highlight the importance of the parameter “time” for new natural products discovery. An untargeted time-scale metabolomic study has been performed on two different marine-derived Penicillium strains. They were cultivated for 18 days and their crude extracts were analyzed by HPLC-DAD-HRMS (High Performance Liquid Chromatography-Diode Array Detector-High Resolution Mass Spectrometry) each day. With the example of gri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 63 publications
1
35
0
1
Order By: Relevance
“…This difference in activity could also be due to difference in fungal biomass on the plugs as they had different times to grow between the samplings. This time-dependent difference in metabolism has been shown for different Penicillium species before (Khalil et al 2014 ; Roullier et al 2016 ).…”
Section: Discussionsupporting
confidence: 68%
“…This difference in activity could also be due to difference in fungal biomass on the plugs as they had different times to grow between the samplings. This time-dependent difference in metabolism has been shown for different Penicillium species before (Khalil et al 2014 ; Roullier et al 2016 ).…”
Section: Discussionsupporting
confidence: 68%
“…227 A study which analysed two Penicillium strains at different time points throughout the culture period by HPLC-DAD-HRMS indicated that a greater chemodiversity of metabolites may be obtained from the one strain by performing extractions at different times throughout the culture period including early and late growth phases. 228 Studies on the effect of light on the biosynthesis of the anticancer polyketide 1403C (haloroquinone, SZ-685C) in Halorosellinia sp., indicated that light signicantly increased production of this metabolite (74%) over production in the dark. 229 Comparison of the secondary metabolite prole of a monoculture of Aspergillus avipes with that of a strain cocultured with a Streptomyces strain isolated from the same marine sediment, indicated that physical contact with the bacterium induced production of six cytotoxic cytochalasans (such as aspochalasin P) in the fungus.…”
Section: Marine-sourced Bacteriamentioning
confidence: 99%
“…The agar samples contained fungal mycelium and/or dinoflagellates in a biofilm and the liquid supernatant contained only P. lima when inoculated (fungal spores traces were observed). To obtain a clear view of metabolites present in both types of extracts, they were profiled by LC-HRMS [41]. For sake of clarity, single strain P. lima culture corresponds to the dinoflagellates with (xenic) or without (axenic) their associated bacteria depending on the presence of antibiotics.…”
Section: Specific Microscale Marine Environment Was Designed For Co-culturementioning
confidence: 99%